Availability, effectiveness and safety of cadaveric and fresh allogeneic skin grafts in pediatric burn care: a review - Lenz, Moritz; Allorto, Nikki; Chamania, Shobha; Schiestl, Clemens; Mohr, Christoph; Boettcher, Michael; Elrod, Julia (Cell and tissue banking, 2025)
Burn injuries in children are a critical public health issue with significant mortality and morbidity. Allogeneic skin grafts, both cadaveric and freshly donated, have been utilized in pediatric burn care since many years, yet their efficacy and safety remain to be systematically assessed. This systematic review (PROSPERO number: CRD42024560654) analyzed studies from 01/2000 to 07/2024 sourced from PubMed. Inclusion criteria targeted RCTs and retrospective studies focused on the use of allogeneic skin grafts in pediatric burn patients. Extracted data were presented in a narrative synthesis and a comprehensive table. Established tools were used for risk of bias assessment. 13 studies were deemed suitable for analysis, with only two qualifying as RCTs. Allogeneic skin grafts have shown promise in managing pediatric burns, especially in resource-limited settings where autografts or skin substitutes are not available. Studies varied in their treatment approaches, with allogeneic grafts often used for more severe burns, suggesting that observed adverse effects may be due to injury severity rather than treatment type. The retrospective nature of the majority suggests a limited level of evidence. Moreover, the heterogeneity among study designs and patient populations makes it difficult to draw definitive conclusions. Allogeneic skin grafts represent a valuable treatment option in pediatric burn care. However, further well-designed RCTs are essential to establish a stronger evidence base for their use and to guide clinical decision-making. The current literature underscores the potential of allogeneic grafts but also the necessity for more nuanced research tailored to pediatric needs.